MICROEMULSIONS: PLATFORM FOR IMPROVEMENT OF SOLUBILITY AND DISSOLUTION OF POORLY SOLUBLE DRUGS - G R, DIXIT; V B, MATHUR (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT This study reviews that solubilization of lipophilic drugs with low aqueous solubility has been a major trust area in recent years. It can be seen that there is a real and continuing need for the development of effective drug delivery systems for poorly water-soluble drugs to enhance their absorption and bioavailability. One such approach might be pharmaceutical microemulsions as they have emerged as potential solubility enhancing technologies. Microemulsion system has considerable potential to act as a drug delivery vehicle by incorporating a wide range of drug molecules. Microemulsion has got advantage like excellent thermodynamic stability, high drug solubilization capacity, improved oral bioavailability and protection against enzymatic hydrolysis. This review focuses on the basic concept, formulation, characterization, and recent advances in microemulsions as novel drug delivery system. Keywords: Microemulsion, Lipophilicity, Solubilization, Bioavailability, Phase behavior.